PENGARUH JENIS KELAMIN REKANAN AUDIT, RISIKO AUDIT DAN KUALITAS AUDIT TERHADAP AUDIT FEE (Studi Empiris pada Perusahaan non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Nursyabrina, Nursyabrina; Achmad, Tarmizi (Diponegoro Journal of Accounting, 2024)
This study aims to analyze the effect of audit partners’ sex, audit risk, and audit quality on audit fees. The population of this study were non-financial companies listed in Indonesia Stock Exchange from 2018 to 2020. In this study, the samples used through purposive sampling method were 372 firm-year data from 124 companies. Data was analyzed using descriptive statistical analysis, overall model fit analysis and hypothesis test. Logistic regression is used to examine the effect of audit partners’ sex, audit risk, and audit quality on audit fees. The results of this analytical study indicate that audit partners’ sex has no effect on audit fees. Meanwhile, audit risk has positive effect on audit fees. The results of this study also indicate that audit quality has positive effect on audit fees.